2017
DOI: 10.1371/journal.pone.0178958
|View full text |Cite
|
Sign up to set email alerts
|

Predictive models for estimating visceral fat: The contribution from anthropometric parameters

Abstract: BackgroundExcessive adipose visceral tissue (AVT) represents an independent risk factor for cardiometabolic alterations. The search continues for a highly valid marker for estimating visceral adiposity that is a simple and low cost tool able to screen individuals who are highly at risk of being viscerally obese. The aim of this study was to develop a predictive model for estimating AVT volume using anthropometric parameters.ObjectiveExcessive adipose visceral tissue (AVT) represents an independent risk factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 32 publications
0
20
1
2
Order By: Relevance
“…In addition, the correlation of anthropometric markers has also been the focus of investigations that point out cardio metabolic risks. (1,7,15,21,(25)(26) Th is study showed that NTR is not the most appropriate measure to estimate MS in a popula- tion of Brazilian university students. However, NC and TC have been shown to be useful in predicting metabolic and cardiovascular dysfunctions related to the progression of diseases such as diabetes, atherosclerotic disease, systemic arterial hypertension, or others involving the accumulation of visceral and subcutaneous adiposity, infl uencing the development of components for MS. (27)(28)(29)(30) In the analysis of the correlation between NTR and MS componentes, it was observed that the establishment of this anthropometric index has a positive impact with almost all, being an excellent indicator of risk through these biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the correlation of anthropometric markers has also been the focus of investigations that point out cardio metabolic risks. (1,7,15,21,(25)(26) Th is study showed that NTR is not the most appropriate measure to estimate MS in a popula- tion of Brazilian university students. However, NC and TC have been shown to be useful in predicting metabolic and cardiovascular dysfunctions related to the progression of diseases such as diabetes, atherosclerotic disease, systemic arterial hypertension, or others involving the accumulation of visceral and subcutaneous adiposity, infl uencing the development of components for MS. (27)(28)(29)(30) In the analysis of the correlation between NTR and MS componentes, it was observed that the establishment of this anthropometric index has a positive impact with almost all, being an excellent indicator of risk through these biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of fat located in the central, peripheral, visceral or subcutaneous region is strongly associated with the risk of developing chronic diseases, such as diabetes, hypertension, dyslipidaemias and coronary diseases, among others closely related to the progression of a group of dysfunctions that determine the Metabolic Syndrome (MS) -a complex disorder represented by a set of cardiovascular and metabolic risk factors related to fat accumulation and insulin resistance. (1)(2)(3) Although university life offers positive educational resources and opportunities that lead to healthy habits, the behaviors presented by university students have been mostly negative and associated with weight gain, higher alcohol consumption, sedentary lifestyle and non-nutritive diets, ideal for the accumulation of obesity and cardiovascular risks for chronic diseases. (4) The question is: what kind of interventions are needed for this population?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that abdominal obesity that is assessed based on waist circumference can play a crucial role in the development of metabolic diseases [16]. Waist circumference provides a better estimate of visceral fat and can be used as an alternative marker for abdominal fat mass [17]. Waist-to-height ratio is another index for measurement of obesity and is used to predict metabolic risks [14].…”
Section: Introductionmentioning
confidence: 99%
“…Visceral fat plays a critical role in MetS pathogenesis (10). Since visceral fat is mainly concentrated in the abdomen, for a long time, people have simply screened and managed visceral obesity through central obesity anthropometric indices, such as waist circumference (WC), body mass index (BMI) and WHtR (11). However, some studies found that these indices provide limited information about fat distribution.…”
Section: Introductionmentioning
confidence: 99%